Bone marrow CCR3 dictates eosinophil lineage commitment of CD34⁺ progenitors to orchestrate allergic rhinitis: A composite study - Zhi-qiang Zhang; Meng-yi Wei; Jia-le Bei; Jing-Yang Li; Mei-na Dai; Yin-li Jiang; Ya-ting Xiao; Ying Zhang; Xinhua Zhu (PLoS ONE, 2026)
Background Allergic rhinitis (AR) is a common Th2-mediated inflammatory disease of the nasal mucosa, in which eosinophils serve as pivotal effector cells. The CCR3 receptor, specific for eotaxin, plays a critical role in allergic inflammation. However, the role of CCR3 in the differentiation of bone marrow CD34 ⁺ progenitor cells into eosinophils and its contribution to AR pathogenesis remains incompletely defined. Objective This study aimed to investigate whether bone marrow cell-specific CCR3 deletion is associated with altered CD34 ⁺ progenitor abundance, eosinophil-lineage–related responses, and allergic inflammation in a murine model of allergic rhinitis. Methods An integrative approach was employed. Bioinformatic analyses of transcriptomic data from CCR3-deficient mice, including differential expression screening, WGCNA, functional enrichment, and six machine learning algorithms, were used to identify candidate genes associated with CCR3 deletion. A bone marrow cell-specific CCR3 conditional knockout (CCR3-CKO) mouse model was generated and subjected to an ovalbumin-induced AR protocol. Nasal symptoms, body weight, nasal mucosal histopathology (H&E, PAS), serum cytokine/mediator levels (IL-5, eotaxin, ECP, EPO), and immune cell populations were assessed. Flow cytometry quantified CD34 ⁺ progenitors, CD34 ⁺ CCR3 ⁺ progenitors, and eosinophils in bone marrow, peripheral blood, and nasal lavage fluid. In vitro transwell migration and eosinophil colony-forming assays were performed to evaluate progenitor cell function. Results Bioinformatic and machine-learning analyses identified CD34 as a candidate hub gene associated with CCR3 deletion. In the AR model, CCR3-CKO mice showed reduced nasal symptom scores, less inflammatory-cell infiltration, and attenuated tissue injury, with a trend toward reduced allergy-associated weight loss. CCR3 deletion was associated with lower CD34 mRNA and protein levels in bone marrow and peripheral blood, as well as reduced proportions of CD34 ⁺ progenitors, CD34 ⁺ CCR3 ⁺ progenitors, and eosinophils across the analyzed compartments. Serum IL-5, ECP, and EPO levels were decreased, whereas eotaxin levels were increased. In vitro, CCR3 deficiency showed a modest reduction in the migratory response of CD34 ⁺ progenitors to eotaxin and partially reduced IL-5/eotaxin-associated eosinophil colony formation. Conclusion Bone marrow cell-specific CCR3 deletion was associated with reduced eosinophil-lineage–related progenitor abundance, decreased eosinophilic inflammation, and partial improvement of AR-associated phenotypes. These findings suggest that the eotaxin/CCR3 axis may contribute to hematopoietic and eosinophil-lineage regulation in allergic inflammation. However, the direct cell-intrinsic regulation of CD34 expression and the relative contribution of IL-5-dependent pathways require further investigation.